Generalized chaplygin gas dominated anisotropic bianchi type-i cosmological models - ShriRam; Zeyauddin M.; Singh C.P. (My University, 2025)
We present Bianchi type-I cosmological models in the presence of generalized Chaplygin gas and perfect fluid for early and late time epochs. Exact solutions of Einstein's field equations for this model are obtained. The general solutions of gravitational field equations are expressed in an exact parametric form, with average scale factor as parameter. In the limiting cases of small and large values of the average scale factor, the solutions of the field equations are expressed in exact analytic forms. Moreover, this model predicts that the expansion of Universe is accelerating for the late times. The physical and geometrical properties of the corresponding cosmological models are discussed. © 2008 Springer Science+Business Media, LLC.